Beyond Instrumentalised Politics : Re-Conceptualising Public Governance. - Thomson, Garrett. (Re-Imagining Public Governance Series, 2024)
The weaknesses of aggregative/representative democracy point to the current governments' failures so prevalent in the West that there are few innovative alternatives. Given that major global challenges all hinge on the transformation of public governance, it has become a most pressing matter for humanity to re-conceptualise future-making approaches to governance. This series aims to explore constructive and promising orientations to democracy.